SCFFBXW7 regulates G2‐M progression through control of CCNL1 ubiquitination. (24th October 2022) - O'Brien, Siobhan; Kelso, Susan; Steinhart, Zachary; Orlicky, Stephen; Mis, Monika; Kim, Yunhye; Lin, Sichun; Sicheri, Frank; Angers, Stephane
Abstract: FBXW7, which encodes a substrate‐specific receptor of an SCF E3 ligase complex, is a frequently mutated human tumor suppressor gene known to regulate the post‐translational stability of various proteins involved in cellular proliferation. Here, using genome‐wide CRISPR screens, we report a novel synthetic lethal genetic interaction between FBXW7 and CCNL1 and describe CCNL1 as a new substrate of the SCF‐FBXW7 E3 ligase. Further analysis showed that the CCNL1–CDK11 complex is critical at the G2‐M phase of the cell cycle since defective CCNL1 accumulation, resulting from FBXW7 mutation, leads to shorter mitotic time. Cells harboring FBXW7 loss‐of‐function mutations are hypersensitive to treatment with a CDK11 inhibitor, highlighting a genetic vulnerability that could be leveraged for cancer treatment. Synopsis: The candidate oncogene CCNL1 is regulated by FBXW7 through ubiquitination and degradation in a Cul1‐dependent manner. FBXW7‐mutant cells depend on CCNL1 for growth, sensitizing them to OTS964, an inhibitor of CCNL1 kinase partner CDK11. FBXW7‐mutant cells depend on CCNL1 for growth. CCNL1 is a novel substrate of FBXW7. CCNL1 mediates mitotic progression and reliance on this signalling axis sensitizes cells to CDK11 inhibitor OTS964. Abstract : The candidate oncogene CCNL1 is regulated by FBXW7 through ubiquitination and degradation in a Cul1‐dependent manner. FBXW7‐mutant cells depend on CCNL1 for growth, sensitizing them to OTS964, an inhibitor of CCNL1 kinase partner CDK11.